Biologic targets identified from dynamic 18FDG-PET and implications for image-guided therapy. (October 2013) - Rusten, Espen; Rødal, Jan; Bruland, Øyvind S.; Malinen, Eirik
Abstract Purpose. The outcome of biologic image-guided radiotherapy depends on the definition of the biologic target. The purpose of the current work was to extract hyperperfused and hypermetabolic regions from dynamic positron emission tomography (D-PET) images, to dose escalate either region and to discuss implications of such image guided strategies. Methods. Eleven patients with soft tissue sarcomas were investigated with D-PET. The images were analyzed using a two-compartment model producing parametric maps of perfusion and metabolic rate. The two image series were segmented and exported to a treatment planning system, and biological target volumes BTVper and BTVmet (perfusion and metabolism, respectively) were generated. Dice's similarity coefficient was used to compare the two biologic targets. Intensity-modulated radiation therapy (IMRT) plans were generated for a dose painting by contours regime, where planning target volume (PTV) was planned to 60 Gy and BTV to 70 Gy. Thus, two separate plans were created for each patient with dose escalation of either BTVper or BTVmet. Results. BTVper was somewhat smaller than BTVmet (209 ± 170 cm3 against 243 ± 143 cm3, respectively; population-based mean and s.d.). Dice's coefficient depended on the applied margin, and was 0.72 ± 0.10 for a margin of 10 mm. Boosting BTVper resulted in mean dose of 69 ± 1.0 Gy to this region, while BTVmet received 67 ± 3.2 Gy. Boosting BTVmet gave smaller dose differences between the respective non-boost DVHs (such as D98). Conclusions. Dose escalation of one of the BTVs results in a partial dose escalation of the other BTV as well. If tumor aggressiveness is equally pronounced in hyperperfused and hypermetabolic regions, this should be taken into account in the treatment planning.